Xây dựng hệ trợ giúp tính toán thông minh - Khang, Trần Đình; Sơn, Nguyễn Quang; Kiếm, Hoàng Văn (Journal of Computer Science and Cybernetics, 2016)
This paper present a method for implementing a toolbox for calculating nonprogrammable that belongs to a new software generation which supports works relating to technical-scientific and economic calulations.